Efficacy of imiquimod 3.75% from Lmax according to the number of actinic keratosis lesions. (28th October 2014) - Peris, K.; Stockfleth, E.; Gupta, G.; Aractingi, S.; Dakovic, R.; Dirschka, T.; Alomar, A.
Abstract: Background: Imiquimod 3.75% reduces 92.2% of all actinic keratosis (AK) lesions, assumed to include both subclinical and clinical lesions, across a large sun‐exposed field such as the full face or balding scalp. Objective: To evaluate the efficacy of imiquimod 3.75% using the reduction in lesions from Lmax (the maximum lesion count during treatment) in subgroups of patients with low and high AK lesion counts. Methods: Patients from two 14‐week, placebo‐controlled, double‐blind studies were subgrouped according to whether they had ≤10 or >10 AK lesions at baseline. Treatment was applied to the full face or balding scalp during two 2‐week treatment cycles separated by a 2‐week treatment‐free interval. Results: Overall, 167 patients had ≤10 lesions and 152 patients had >10 AK lesions at baseline. With imiquimod 3.75%, the median percentage reduction in AK lesions from Lmax to end of study was similar in patients with ≤10 and >10 baseline lesions (91.5% and 93.0% respectively). The median absolute reduction in AK lesions from Lmax to end of study was 24.0 for patients with >10 baseline lesions and 10.0 for those with ≤10 baseline lesions. The median percentage and absolute reductions in lesions from Lmax were significantly greater with imiquimod 3.75% vs. placebo ( P < 0.0001). Conclusions: Imiquimod 3.75% is effective regardless of disease severity as shown in this study by the reduction of over 90% of lesions from Lmax in patients with low or high AK lesion counts.